Effects of Sugars and Aminooxyacetic Acid on the Longevity of Pollinated Oncidium Gower Ramsey Flowers - S, Chandran; R, Zuliana; Y.K, Yip; H, Nair; B.A, Nasrulhaq; Y.N, Tiew (Malaysian Journal of Science, 2007)
The effects of sugars and aminooxyacetic acid (AOA) on the vase life of pollinated Oncidium Gower Ramsey flowers were investigated in this study. AOA was found to be an effective ethylene inhibitor as holding solutions containing 0.5 mM of AOA considerably prolonged the vase life of the flowers. The best treatment in delaying the senescence of pollinated Oncidium Gower Ramsey flowers were solutions of 4% sucrose + 0.5 mM AOA and 0.5 mM AOA. Both these treatments managed to delay the discolouration, furrowing and appearance of the veins up to nearly twice the length of time it took for the control flowers held in distilled water, to start senescing. The addition of glucose to the holding solution was not as effective as sucrose in delaying the senescence and prolonging the vase life of the flowers. Signs of senescence such as discolouration were measured using the Minolta chroma meter. Weight loss and pH of the holding solutions were also measured daily. AOA added in the solutions had a positive effect of lowering the pH of the holding solution thus inhibiting bacterial growth in the vial. A low pH also accounted for better water uptake by the flowers which delayed turgor loss and thus also delaying the wilting of the flowers.